First Record of Phlebotomus (Larroussius) perfiliewi (Diptera: Psychodidae), Vector of Leishmania infantum and Phleboviruses, in Spain - Mikel A. González; Ignacio Ruiz-Arrondo; Rafael Gutiérrez-López; Carlos Barceló; Miguel Á. Miranda (Diversity, 2023)
Phlebotomine sand flies are vectors of several diseases of importance for public health, including leishmaniosis, bartonellosis, and sand fly fevers. An entomological survey on blood-feeding Diptera was conducted in June–November 2020–2021 to know the diversity of insect vectors in Mallorca (Balearic Islands, Spain). Among the vectors collected, Phlebotomus (Larroussius) perfiliewi Parrot, 1930 was found being the first record of this species in Spain. Phlebotomus perfiliewi s.l. is one of the main vectors of Leishmania infantum in the Mediterranean Basin and Central Asia. The identification of this species was confirmed by both morphological features and DNA barcoding. Phylogenetic analyses showed that the specimens captured were Ph. perfiliewi s.s. (99.85–100% homologues from Italy and Algeria specimens), with a sequence divergence of 0.17%. The cytochrome c oxidase subunit I gene clearly separates the three species that make up the Ph. perfiliewi species complex. In addition, we also provide a brief discussion about their identification remarks, phylogenetic relationships, and vector status.